A Near‐Infrared Laser‐Activated "Nanobomb" for Breaking the Barriers to MicroRNA Delivery. Issue 2 (16th November 2015) - Wang, Hai; Agarwal, Pranay; Zhao, Shuting; Yu, Jianhua; Lu, Xiongbin; He, Xiaoming
Abstract : A near‐infrared laser‐activated "nanobomb" is synthesized using lipid and multiple polymers to break the extracellular and intracellular barriers to cytosolic delivery of microRNAs. The nanobomb can be used to effectively destroy tumors and cancer stem‐like cells in vitro and in vivo with minimal side effects.